2003
DOI: 10.1002/mrdd.10075
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐based morphometric analysis of typical and atypical brain development

Abstract: The neuroinformatics landscape in which human brain morphometry occurs has advanced dramatically over the past few years. Rapid advancement in image acquisition methods, image analysis tools and interpretation of morphometric results make the study of in vivo anatomic analysis both challenging and rewarding. This has revolutionized our expectations for current and future diagnostic and investigative work with the developing brain. This paper will briefly cover the methods of morphometric analysis that availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Other studies have investigated gross anatomical structural differences in brain morphology as a potential biological phenotype for dyslexia (see Kennedy et al, [2003] in this issue for overview of MRI and its use in morphometry studies of development). Several early publications reported that dyslexia is marked by a lack of the normal asymmetry in planum temporale, which might serve as such a phenotypic marker [Galaburda et al, 1985;Rumsey et al, 1986].…”
Section: Anatomical Contributionsmentioning
confidence: 98%
“…Other studies have investigated gross anatomical structural differences in brain morphology as a potential biological phenotype for dyslexia (see Kennedy et al, [2003] in this issue for overview of MRI and its use in morphometry studies of development). Several early publications reported that dyslexia is marked by a lack of the normal asymmetry in planum temporale, which might serve as such a phenotypic marker [Galaburda et al, 1985;Rumsey et al, 1986].…”
Section: Anatomical Contributionsmentioning
confidence: 98%
“…Therefore, MRI has also provided an opportunity to investigate healthy children and thereby has markedly improved data about normal brain development (Kennedy, Haselgrove, & McInerney, 2003).…”
Section: Mri As a Neuroimaging Technique In Childhoodmentioning
confidence: 99%
“…In general researchers collect at least one set of structural images to allow localization of the functional activations. In our lab we collect a high resolution 3D volume [for anatomical studies similar to those described in Kennedy et al, 2003, in this issue] as well as a set of in-plane images that cover the whole brain and that are used for localizing the functional activity. For the functional data collection, imaging tasks typically are organized into a number of discrete 'runs' with rest breaks in between.…”
Section: Paradigm Developmentmentioning
confidence: 99%